2019
DOI: 10.1049/htl.2018.5020
|View full text |Cite
|
Sign up to set email alerts
|

Selective stimulation of rat sciatic nerve using an array of mm‐size magnetic coils: a simulation study

Abstract: This work proposes and computationally investigate the use of magnetic neural stimulation as an alternative to electrical stimulation to achieve selective activation of rat sciatic nerve. In particular, they assess the effectiveness of an array of small coils to obtain selective neural stimulation, as compared to a single coil. Specifically, an array of four mm-sized coils is used to stimulate rat sciatic nerve, targeting the regions of fascicles that are associated with different muscles of the leg. To evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…The first would be to include a threshold for DTDI (e.g., DTDI ≥ 0.75) as a precautionary measure when individualizing the current dose. We recommend this value because studies pertaining to peripheral nerve stimulation have also found that such a threshold value (≥ 0.75) for the ‘selectivity index’ could ensure that the targeted region of the nerve is well activated [ 28 , 30 ]. While this may narrow down the suitability of subjects, such inclusion criteria could reduce the variability of tDCS.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The first would be to include a threshold for DTDI (e.g., DTDI ≥ 0.75) as a precautionary measure when individualizing the current dose. We recommend this value because studies pertaining to peripheral nerve stimulation have also found that such a threshold value (≥ 0.75) for the ‘selectivity index’ could ensure that the targeted region of the nerve is well activated [ 28 , 30 ]. While this may narrow down the suitability of subjects, such inclusion criteria could reduce the variability of tDCS.…”
Section: Discussionmentioning
confidence: 99%
“…It has been found that some brain regions may act as conduits, clustering most of the current to a specific location that can deter the intensity of the stimulation expected at the target ROI [ 6 , 26 ]. At this point, it is important to mention that other stimulation techniques (like peripheral nerve stimulation) are also intended to increase the stimulation intensity at target region while minimizing the stimulation received at non-target regions [ 27 , 28 , 29 , 30 ]. With tDCS, poor focality in stimulating the target region has constrained its efficacy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This maximizes patient comfort and also eliminates risks from potential surgical interventions. Another advantage compared to electric stimulation is the relatively uniform distribution of magnetic permeability in the tissue, which makes it possible to control the magnetic field distribution precisely [18]. However, one large disadvantage comes from the fact that a considerably higher amount of energy is required for magnetic stimulation, therefore devices are large and expensive.…”
Section: Introductionmentioning
confidence: 99%
“…The age cut-off points of the present sample were kept same as in our previous study (Kashyap et al, 2021) to have a consistency in the findings. Although the threshold of DTDI at 0.75 was inspired from previous nerve stimulation studies that found this threshold to be optimal in stimulating the target region (Tigra et al, 2016;Kosta et al, 2019), additional analysis was performed here to determine the optimality of DTDI (please see methods section "Additional analysis of focality").…”
Section: Introductionmentioning
confidence: 99%